2019
DOI: 10.1155/2019/2403024
|View full text |Cite
|
Sign up to set email alerts
|

Resolving a Multi-Generational Neuromuscular Mystery in a Family Presenting with a Variable Scapuloperoneal Syndrome in a c.464G>A, p.Arg155His VCP Mutation

Abstract: Valosin containing protein (VCP) mutations have been reported to present with a high degree of variability and can be present in patients even if they may have an initial normal work up. A 55-year-old woman was labeled as “normal” and “pain medication seeking” after an unrevealing work up of clinical, laboratory, electrodiagnostic, radiographic, pathologic, and genetic testing. She continued to present with chronic neck pain, and had variable features of scapuloperoneal atrophy, which was also seen in her fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Subsequent cohorts confirmed this triad as common in patients with mutations in the VCP gene but also extended the phenotype to involvement of the CNS, motor neurones, sensory and/or motor peripheral nerves and the skeletal muscle 1 7 10 13 16–21 33–36. Our study confirms that muscle weakness, affecting both proximal or distal muscles of the lower and/or upper limbs, is the main symptom at onset, turning MSP into a challenging diagnosis whereas patients can be classified as having limb girdle muscle weakness, distal myopathy or scapuloperoneal syndrome 37…”
Section: Discussionsupporting
confidence: 78%
“…Subsequent cohorts confirmed this triad as common in patients with mutations in the VCP gene but also extended the phenotype to involvement of the CNS, motor neurones, sensory and/or motor peripheral nerves and the skeletal muscle 1 7 10 13 16–21 33–36. Our study confirms that muscle weakness, affecting both proximal or distal muscles of the lower and/or upper limbs, is the main symptom at onset, turning MSP into a challenging diagnosis whereas patients can be classified as having limb girdle muscle weakness, distal myopathy or scapuloperoneal syndrome 37…”
Section: Discussionsupporting
confidence: 78%
“…We performed a literature review on the clinical and genetic characteristics of previously reported ALS‐VCP cases (Table S1), 2,4–7,16,23–33 and illustrated mutation sites in VCP associated with ALS, IBMPFD, and other phenotypes (Figure S1). 2–5,7,16,20–86 A total of 59 cases have been reported, with the disease typically developing in patients in their 40s–50s, and 14 of the 33 cases survived without artificial respiration for more than five years. Given that the epidemiological studies of general ALS suggest that the peak prevalence is observed in patients in their 70s–80s, and that the median survival time is two to four years, 87–91 the ALS‐VCP cases might be characterized by relatively early disease onset and slow disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…The most common VCP /p97 mutations include R155H, R155C, R159H, and R93C [ 4 ]. To date, additional VCP variants have been reported, a few of which were classified as variants of unknown significance that were not previously associated with human disease [ 3 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Here, we report multiple previously undescribed likely pathogenic variants in the VCP gene that were identified in five patients, three from the same family.…”
Section: Introductionmentioning
confidence: 99%